Serviço de referência digital: uma análise apoiada em agentes de interface - Moreno, Patrícia da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2005)
The electronic environment for the dispose of information is frequently incorporating the services offered by the libraries, aiming to provide means to find information and documents in electronic nets. However, many users have difficulties in the interaction with certain interfaces, which turns the search for information uninteresting and, most of the time, stressful. That way, alternatives are being searched to turn the human-computer interfaces more friendly and intelligent. The development and use of interface agent systems are good alternatives to minimize this type of problem. These systems function to interact with the user, as if they were characters that help in the accomplishment of certain tasks. In that sense, the objective of this research is to analyze and develop an interface agent that acts as a reference agent in a simulated website of a library, offering a personalized search service starting from the user's relationships with a digital system. The interface agent, having the information provided by the users, will build a search strategy that determines the significant words of a text presented by the user and will act as a researcher in catalogs of available libraries on Internet and in the Google index in order to offer answers to the solicitations. With the application of the interface agent the author intends to evaluate the performance of this type of software as a facilitator of the user's interaction with available collections, through digital catalogs, not as a mere illustration, but as a personal assistant in the information search process, as well as to verify through experiments with the prototype, based on the heuristic evaluation methodology, which actions should be taken for the correction of mistakes that affect the interface usability, confirming the hypothesis of effectiveness of a system of that nature... (Complete abstract, click electronic address below)

O ambiente eletrônico para a disponibilização de informações vem incorporando com freqüência os serviços oferecidos pelas bibliotecas, procurando proporcionar facilidades na localização de informações e de documentos nas redes eletrônicas. Entretanto, muitos usuários encontram dificuldades na interação com certas interfaces, o que torna a busca por informações desestimulante e muitas vezes estressante. Deste modo, buscam-se alternativas para tornar as interfaces humano-computador mais amigáveis e inteligentes. O desenvolvimento e utilização de sistemas de agentes de interface apresentam-se como uma boa opção para minimizar este tipo de problema. Estes sistemas têm como função interagir com o usuário, como se fossem personagens que auxiliam na realização de determinadas tarefas. Nesse sentido, o objetivo desta pesquisa é analisar e desenvolver um agente de interface que atuará como um agente de referência em um site simulado de uma biblioteca oferecendo um serviço de busca personalizado a partir das relações do usuário com um sistema digital. O agente de interface, possuindo as informações fornecidas pelos usuários, construirá uma estratégia de busca que determina as palavras significativas do texto apresentado pelo usuário e passa a atuar como um pesquisador em catálogos de bibliotecas disponíveis na Internet e no índice Google para oferecer respostas às solicitações. Com a aplicação do agente de interface pretende-se avaliar a atuação deste tipo de software como facilitador da interação do usuário com acervos disponíveis, via catálogos digitais, não como mera ilustração, mas como um assistente pessoal no processo de busca à informação. E ainda verificar através do experimento com o protótipo, baseado na metodologia de avaliação heurística quais ações deverão ser tomadas para a correção dos erros que afetam a...
Keywords: Recuperação da informação - Bibliotecas digitais; Recuperação da informação - Interfaces (Computador); Interação homem-maquina; Serviço de referência digital; Usabilidade de interfaces; Agentes de interface; Interface usability; Digital reference service; Interface agent; Human computer interaction